Quality dating: a well-defined protocol implemented at ETH for high-precision 14C-dates tested on late glacial wood - Sookdeo, Adam; Kromer, Bernd; Büntgen, Ulf; Friedrich, Michael; Friedrich, Ronny; Helle, Gerhard; Pauly, Maren; Nievergelt, Daniel; Reinig, Frederick; Treydte, Kerstin; Synal, Hans-Arno; Wacker, Lukas (Radiocarbon, 2020)
Advances in accelerator mass spectrometry have resulted in an unprecedented amount of new high-precision radiocarbon (14C) -dates, some of which will redefine the international 14C calibration curves (IntCal and SHCal). Often these datasets are unaccompanied by detailed quality insurances in place at the laboratory, questioning whether the 14C structure is real, a result of a laboratory variation or measurement-scatter. A handful of intercomparison studies attempt to elucidate laboratory offsets but may fail to identify measurement-scatter and are often financially constrained. Here we introduce a protocol, called Quality Dating, implemented at ETH-Zürich to ensure reproducible and accurate high-precision 14C-dates. The protocol highlights the importance of the continuous measurements and evaluation of blanks, standards, references and replicates. This protocol is tested on an absolutely dated German Late Glacial tree-ring chronology, part of which is intercompared with the Curt Engelhorn-Center for Archaeometry, Mannheim, Germany (CEZA). The combined dataset contains 170 highly resolved, highly precise 14C-dates that supplement three decadal dates spanning 280 cal. years in IntCal, and provides detailed 14C structure for this interval.